ADAPTING GOOGLE MAPS AS THE SOURCE OF SPEAKING MATERIAL FOR EOP STUDENTS - Novi Indriyani; Rezky Uspayanti (PT Akselerasi Karya Mandiri, 2023)
This paper is addressed to promote one of the teaching-learning materials for EOP students by considering several appropriate material developments. Speaking subject becomes the layout of this research, and Google Maps is chosen to be adapted into their learning material. The writer started the procedure with several steps, such as planning the sequence of learning components, the adaptation process, and inserting preferable tasks. Thus, along with the procedures, the material is added by several linguistic features such as vocabulary, grammar, and dialogue. Halfway through the material construction, the writer completes it with a preferable task to enhance the opportunity to perform the language. The selection of Google Maps as speaking material is viewed as having a strong relevance to the EOP context, which means it can impact their involvement in the process of learning language a lot.